Rabies surveillance in dogs in Lao PDR from 2010-2016 - Douangngeun, B; Theppangna, W; Phommachanh, P; Chomdara, K; Phiphakhavong, S; Khounsy, S; Mukaka, M; Dance, D; Blacksell, S (Public Library of Science, 2017)
BACKGROUND: Rabies is a fatal viral disease that continues to threaten both human and animal health in endemic countries. The Lao People's Democratic Republic (Lao PDR) is a rabies-endemic country in which dogs are the main reservoir and continue to present health risks for both human and animals throughout the country. METHODS: Passive, laboratory-based rabies surveillance was performed for suspected cases of dog rabies in Vientiane Capital during 2010-2016 and eight additional provinces between 2015-2016 using the Direct Fluorescent Antibody Test (DFAT). RESULTS: There were 284 rabies positive cases from 415 dog samples submitted for diagnosis. 257 cases were from Vientiane Capital (2010-2016) and the remaining 27 cases were submitted during 2015-2016 from Champassak (16 cases), Vientiane Province (4 cases), Xieng Kuang (3 cases), Luang Prabang (2 cases), Saravan (1 case), Saisomboun (1 case) and Bokeo (1 case). There was a significant increase in rabies cases during the dry season (p = 0.004) (November to April; i.e., <100mm of rainfall per month). No significant differences were noted between age, sex, locality of rabies cases. CONCLUSION: The use of laboratory-based rabies surveillance is a useful method of monitoring rabies in Lao PDR and should be expanded to other provincial centers, particularly where there are active rabies control programs.